(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The idea of shared virtual currencies is revolutionary. Cryptocurrencies. It has proved to be a modern investing opportunity close to gold in India. While the government has not devised any legislative authority or regulations on cryptocurrecny in India, it is regulating the buying and selling of cryptocurrencies such as bitcoin, litcoin etc. The presence of Cryptocurrencies in Indian markets is subject to numerous prohibitions. The key emphasis of this analysis is on recognising the blockchain in the Indian economy. The report also focuses on the existing status of cryptocurencies in India and their future prospects.